Pendayagunaan Aplikasi Keuangan melalui Metode Prototipe dalam Meningkatkan Pengelolaan Keuangan Pondok Pesantren Berdasarkan Pedoman Akuntansi Pesantren - Prasetyo, Henri (Eksos, 2023)
Sindo.news reported that the financial reports of hundreds of Islamic boarding schools in South Sumatra were considered to be still poor and not up to standards by the Indonesian Accountants Association. This reflects the majority of Islamic boarding schools are still inadequate in financial management. Based on this, researchers are trying to take part in improving Islamic boarding school financial management by building financial applications that comply with Islamic Boarding School Accounting Guidelines and the wishes of application users. The design and implementation of financial applications will use the prototype method, due to the high level of change in terms of regulations and stakeholder desires from Islamic boarding schools. The wishes of application users are proxied through suggestions and criticism from Al I'tishom Kubu Raya Islamic Boarding School. The financial application built uses a web-based application using the HTML, CSS, Javascript, and PHP programming languages ​​processed by the XAMPP program. Then the database used is MySQL and the text editor used is Notepad++. This research produces criteria that need to be adjusted to produce database and program designs that comply with Islamic Boarding School Accounting Guidelines. These criteria are expressed through 3 aspects: recognition and measurement; presentation; and disclosure. The recognition and measurement aspect stipulates that Islamic boarding schools must record all financial transactions, both transactions and non-cash, that can be measured at the rupiah exchange rate. Then the presentation aspect is determined that Islamic boarding schools must be able to present the financial reports mentioned in the Islamic Boarding School Accounting Guidelines. Finally, the disclosure aspect stipulates that Islamic boarding schools must disclose detailed financial reports. The results of the application modification present four main menus that focus on adjusting the specified criteria. The four menus are receipt input, expenditure input, journal input, and print report. The income and expenditure input menu can sort the funds used into three, namely: unrestricted funds, restricted funds, and non-halal funds. Journal input is used to accommodate non-cash transactions carried out by Islamic boarding schools. The results of all input will be collected to produce a report in the print report menu. Adapting the application to the user's wishes makes the application usable even if there is no internet access. The final result of the research produced an IPR certificate called "Ai-Lemdik".